THE CAPITAL REQUIREMENTS OF MSMEs BEFORE AND AFTER PANDEMIC COVID-19 (CASE STUDY ON SMEs IN BAUBAU CITY) - Fajar Rakasiwi Syamsuddin (Jurnal Ekonomi, 2023)
Capital requirements are an important factor in the process of survival and adaptation. This study aims to determine the difference in the level of capital needs for MSME actors before the pandemic, during the pandemic and after the pandemic in 2021. The research method used is a quantitative method with the analytical tool for testing the hypothesis is the average difference test or t-test (t-test). The study was conducted on 84 respondents from 8,322 MSME actors who were successfully recorded by the Department of Cooperatives and MSMEs in Baubau City. The results showed that there was a significant difference in the level of capital requirements for MSME actors in Baubau City before the pandemic in 2019 and during the pandemic in 2020. Besides that, it was also found that there was no significant difference in the level of capital requirements for MSME actors in Baubau City before the pandemic in 2019 and during the pandemic in 2021. Capital requirements are an important factor in the process of survival and adaptation. This study aims to determine the difference in the level of capital needs for MSME actors before the pandemic, during the pandemic and after the pandemic in 2021. The research method used is a quantitative method with the analytical tool for testing the hypothesis is the average difference test or t-test (t-test). The study was conducted on 84 respondents from 8,322 MSME actors who were successfully recorded by the Department of Cooperatives and MSMEs in Baubau City. The results showed that there was a significant difference in the level of capital requirements for MSME actors in Baubau City before the pandemic in 2019 and during the pandemic in 2020. Besides that, it was also found that there was no significant difference in the level of capital requirements for MSME actors in Baubau City before the pandemic in 2019 and during the pandemic in 2021.